Success factors of marketing strategy in real estate business / Adlan Ahmad Bakri, Siti Hasniza Rosman and Suhana Ismail - Ahmad Bakri, Adlan; Rosman, Siti Hasniza; Ismail, Suhana (Universiti Teknologi MARA, 2021)
In the era of the industrial revolution 4.0, it can be seen that real estate development is growing rapidly on the high demand for real estate in various types. Real estate developers are the important actors in the business cycle of real estate industry. The society's perspective in real estate business is for future investment purposes. However, there are also problems with unsold properties due to lack of effective marketing strategies. The researchers have identified the two (2) main objectives; 1) to identify the success factors of marketing strategy in real estate business; and 2) to develop the conceptual framework for success factors of marketing strategy in real estate business. This research paper will unravel the factors that influence successful marketing strategy in the field of real estate by conducting a comprehensive literature review to identify the success factors that need to be considered in forming a quality and best marketing strategy.